Reintroduction of the European bison (Bison bonasus) in central-eastern Europe: a case study. Issue 8 (2nd August 2020) - Lord, Cathlin M.; Wirebach, Kylie P.; Tompkins, Jennifer; Bradshaw-Wilson, Casey; Shaffer, Christopher L.
ABSTRACT: European bison ( Bison bonasus ), a flagship species for the burgeoning re-wildling movement, faced challenges common to large mammals globally. These include deforestation, land use conversion, poaching, and a lack of genetic diversity. Despite these limitations, organizations such as Rewilding Europe seek to reintroduce the species to its historic range. This study focused on finding suitable reintroduction locations for a population of at least 120 individuals. Through GIS-based multi-criteria decision-making using weighted linear combination and analytical hierarchy process, a model based on known bison habitat preferences, human-centered habitat constraints, and surface geography was used to identify regions large enough to accommodate a new herd. The study area included central-eastern Europe Union countries, specifically Germany, Poland, Lithuania, and Latvia. The model identified several highly suitable regions large enough to support a new herd, with the most optimal located in Poland. Highly suitable areas represented 2.7% of the study region. Relative isolation of suitable regions reinforced the challenges of promoting gene flow between reintroduced European bison herds. This model can be replicated in other conservation planning contexts, including reintroduction of large herbivores considering anthropogenic, ecological, and physical conditions.